P.071 Multi-parametric MRI at 7 T enables differentiation of MS and age-related white matter lesions. (2nd June 2017) - Wing Marques dos Santos, A; Hosseini, Z; Drangova, M; Rudko, D; Matusinec, J; Menon, R; Kremenchutzky, M
Abstract : Background: MRI criteria are used to support multiple sclerosis diagnosis and evolution. However, normal age-related lesions (ARLs) can be cofounded with MS white matter lesion (MSL).Methods: Two Multiparametric 7T MRI scans 4 motnhs apart from 5 relapsing MS (RMS) patients were analyzed and compared to 5 matched healthy controls (HC) aiming to differentiate MSLs from ARLs. Six-echo GRE, FLAIR and MPRAGE sequences were acquired.Results: Average size of ARLs was 51 mm3 and of MSLs was 69 mm3 (p=0.27). Both have the same general appearance on FLAIR and MPRAGE contrasts, but different contrast on the R2* and QS maps. Inter-visit variation on MPRAGE was significantly higher in MSLs. Inter-visit signal change in the other contrasts (QSM, R2* and FLAIR) was not significant.Conclusions: R2*, QS maps and inter-visit variation using MPRAGE allowed differentiating MSLs from ARLs in 5 RMS with mean long term disease duration. This could improve correct early diagnosis and accurate lesion load accumulation evolution.